Behavioral factors influencing childhood obesity: a systematic review and meta-analysis. Issue 2 (March 2020) - Poorolajal, Jalal; Sahraei, Fatemeh; Mohamdadi, Younes; Doosti-Irani, Amin; Moradi, Leila
Abstract: Background: This report provides information on 14 behavioral and nutritional factors that can be addressed in childhood overweight/obesity prevention programs. Methods: Web of Science, PubMed, and Scopus were searched through November 2018. Reference lists were also screened for additional references. Observational studies addressing the associations between overweight/obesity in children/adolescents aged between 5 to 19 years and associated risk factors were analyzed. Between-studies heterogeneity was assessed by χ 2, τ 2, and I 2 statistics. The likelihood of publication bias was evaluated using the Begg and Egger tests and trim & fill analysis. Effect sizes were expressed as odds ratios (ORs) with 95% confidence intervals (CIs) using a random-effects model. Results: Of 34, 537 retrieved studies, 199 including 1, 636, 049 participants were eligible. The ORs (95% CI) of factors associated with childhood overweight/obesity were as follows: sufficient physical activity 0.70 (0.66, 0.75); eating breakfast every day 0.66 (0.59, 0.74); sufficient consumption of fruits/vegetables 0.92 (0.84, 1.01); breastfeeding <4 months 1.24 (1.16, 1.33); inadequate sleep 1.26 (1.13, 1.40); watching TV >1–2 h/day 1.42 (1.35, 1.49); playing computer games >2 h/day 1.08 (0.95, 1.23); eating sweets ≥3 times/week 0.78 (0.71, 0.85); eating snack ≥4 times/week 0.84 (0.71, 1.00); drinking sugar-sweetened beverages ≥4 times/week 1.24 (1.07, 1.43); eating fast-food ≥3 times/week 1.03 (0.89, 1.18); eating fried-food ≥3 times/week 1.09 (0.90, 1.33); smoking 1.17 (1.07, 1.29); and drinking alcohol 1.05 (0.95, 1.16). Conclusions: This meta-analysis provided a clear picture of the behavioral and nutritional factors associated with weight gain in children.